Nutritional profile of indigenous children under five years of age in the Upper Solimões River, Amazonas, Brazil (2013) - Francinara Guimarães Medeiros; Evelyne Marie Therese Mainbourg; Aline Alves Ferreira; Antônio Alcirley da Silva Balieiro; James R. Welch; Carlos E. A. Coimbra Jr (Instituto Materno Infantil de Pernambuco, 2023)
Abstract Objectives: to characterize the nutritional status of indigenous children underfive years of age living in rural communities in the Upper Solimões River region, inhabited by seven ethnic groups, based on data of december 2013. Methods: weight and height data extracted from SISVAN-I (Indigenous Food and Nutritional Surveillance System) forms filled in 2013 for 7,520 children (86.0% of the estimated children in this age group). The indices height-for-age (H/A), weight-for-age (W/A), weight-for-height(W/H), and body mass index-for-age (BMI/A) were calculated. Growth reference curves proposed by the World Health Organization were used to calculate z-scores. Results: the height-for-age (H/A) index presented the lowest mean z-score values, reaching -1.95 among children between 36 and 60 months. Mean z-score values for the weight-for-age (W/A) index also remained below zero. Mean z-score values for the indices weight-for-height (W/H) and body mass index-for-age (BMI/A) remained slightly above zero, reaching a maximum value of 0.5. Of all children, 45.7% presented low H/A, 9.6% presented low W/A, 4.5% presented low W/H, and 10.7% presented overweight based on BMI/A. Conclusion: our analysis show that in 2013 poor nutritional status persisted as an important health issue among these rural indigenous children.